The Efficiency of E-Procurement in Malaysia: An Analysis of Experience and Perception - Alaweti, MF; Azizan, N; Faryadi, Q (Int Business Information Management Assoc-Ibima, 2024)
The technology of e-procurement become more popular in many developed countries due to its accuracy in decision making for big projects that enhance the public bidding process for development projects in any country. The experience of employees who operate the system of e-procurement and the perception of users who bid for projects is essential to ensure the efficiency of procurement and the whole bidding process for public projects. This paper examined the impact of employee's experience on the efficiency of e-procurement systems in public agencies. In addition to that attempt to examine the perception factor of using e-procurement systems with regard to users in the seller side. A survey was conducted to identify the Impact of Experience and Perception on the Efficiency towards adoption and use of e-Procurement system among users who working in firms participated in online bidding for public agencies projects, and employees who are working in e-procurement department in government administrations Malaysian government. A total of 80 questionnaires were collected and the data were analyzed to look at the level of the Impact of experience and perception in E-procurement users. The general findings indicate a Positive attitude experience and perception among the users in using the e-procurement.